Faktor Risiko Lingkungan dan Perilaku Yang Berkaitan Dengan Kejadian Malaria di Pangkalbalam Pangkalpinang - Sunarsih, Elvi; Nurjazuli, Nurjazuli; Sulistiyani, Sulistiyani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2009)
ABSTRACT Background: Area of Pangkalpinang health center was an endemic area of malaria which had a fluctuative annual malaria incidence (AMI) from the year of 2004 to 2007 with AMI for each year was about 33,45 ‰; 39,29 ‰; 23,96 ‰; and 24,51 ‰. These condition might be related to environmental and behavioral factors. This research aimed to analyze environmental and behavioral factors in relation to malaria incidence in Pangkalbalam Pangkalpinang. Method: It was an observational research using case-control design. The subjects of the research were divided into two groups, namely cases (68 subjects) and control (68 subjects). Cases were defined and based on the positive blood examination of plasmodium, and controls were the negative blood examination. Behavioral factors measured in this research consisted of the night going out habit, mosquito coil usage, bed net usage, and traveling history to another endemic area of malaria. Environmental factors observed was the existence of ventilation screen, vegetation around the house, characteristic and condition of wall, ceiling, and water bodies around the house. Data would be analyzed using chi-square and multiple logistic regression analysis at 5% level of significance. Result: The result showed that the climate in Pangkalpinang city supported the development and survival of mosquitoes as malaria vector. The mean of temperature was 24,90C, humidity 83%, rainfall 213,4 mm, and wind speed was 3,0 m/s. There were 4 variables as potential factors contributing malaria incidence based on the bivariate analysis, but only 3 variables as risk factors contributing to malaria incidence by multiple logistic regression: the night going out habit, traveling history to another endemic area of malaria, and the existence of water bodies around the house which each Odds Ratio of 3,454; 3,901; and 3,446. Conclusion: The habit of hanging out at night and traveling history to another endemic area of malaria were suggested as behavioral risk factors and the existence of water bodies or ponds around the house was suggested as environmental risk factor. Key words: Behavioral and environmental risk factors, malaria, Pangkalpinang.